Pristimerin Promotes Ubiquitination of HSPA8 and Activates the VAV1/ERK Pathway to Suppress TNBC Proliferation - Qin‐Wen Liu; Qi‐Ling Fan; Jia‐Ying Chen; Jing‐Xin Liu; Yi Li; Qian Luo; Yu‐Peng Chen; Hang‐Tian Wu; An‐Qi Xu; Sheng Wang; Ai‐Ping Lu; Dao‐Gang Guan (Advanced Science)
Abstract Triple‐negative breast cancer (TNBC) is a subtype of breast cancer with a poor prognosis. The natural compound pristimerin has shown promising anti‐tumor effect. Here, it is found that pristimerin significantly triggered the activation of autophagy initiation and induced apoptosis in TNBC. Mechanistically, RNA sequencing revealed that pristimerin activated mitogen‐activated protein kinase/extracelluar regulated protein kinases (MAPK/ERK) pathway. Drug affinity responsive target stability and mass spectrometry techniques are employed to confirm the direct binding target of pristimerin. Heat shock protein family A member 8 (HSPA8) is identified and verified by cellular thermal shift assays and surface plasmon resonance assays. The further results suggested that pristimerin promoted the ubiquitination and degradation of HSPA8, leading to a decrease in the degradation of Vac Guanine Nucleotide Exchange Factor 1 (VAV1), a downstream client protein of HSPA8 which plays a crucial role in activating the ERK pathway. Importantly, knockdown of HSPA8 or VAV1 significantly impaired the anticancer activity of pristimerin on TNBC cells. Additionally, pristimerin significantly inhibited the migration and invasion of TNBC cells and enhanced the sensitivity of TNBC cells to doxorubicin. Collectively, this study provides the initial evidence that pristimerin directly targets HSPA8 to activate the VAV1/ERK pathway, thereby promoting cell autophagy and apoptosis.